2021
DOI: 10.3390/ma14010232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equal Channel Angular Pressing on the Dynamic Softening Behavior of Ti-6Al-4V Alloy in the Hot Deformation Process

Abstract: To investigate the effect of equal channel angular pressing (ECAP) on the deformation of Ti-6Al-4V alloy at a higher temperature, hot compression tests were conducted on alloys having two different initial microstructures (the original alloy (Pre-ECAP) and ECAP-deformed alloy (Post-ECAP)). Post-ECAP, the alloy showed a higher degree of dynamic softening during the hot deformation process due to its finer grain size and higher distortion energy. The flow stress of Post-ECAP alloy was higher than the Pre-ECAP al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Zhao et al preheated the sample to 923 K for 5 min before extrusion and carried out nonisothermal ECAP with the extrusion rate of 20 mm/s and B C route. They found that the average grain size of titanium alloys decreased from 15-20 µm to 5-10 µm and from 30 µm to 10 µm after four passes of ECAP, respectively [32,33]. Jahadi et al reported that the grain size of magnesium alloys was reduced from the initial 20.4 µm to 3.9 µm after four passes of ECAP at 275 • C [34].…”
Section: Grain Size From 1 To 10 µMmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhao et al preheated the sample to 923 K for 5 min before extrusion and carried out nonisothermal ECAP with the extrusion rate of 20 mm/s and B C route. They found that the average grain size of titanium alloys decreased from 15-20 µm to 5-10 µm and from 30 µm to 10 µm after four passes of ECAP, respectively [32,33]. Jahadi et al reported that the grain size of magnesium alloys was reduced from the initial 20.4 µm to 3.9 µm after four passes of ECAP at 275 • C [34].…”
Section: Grain Size From 1 To 10 µMmentioning
confidence: 99%
“…10 μm after four passes of ECAP, respectively [32,33]. Jahadi et al reported that the grain size of magnesium alloys was reduced from the initial 20.4 μm to 3.9 μm after four passes of ECAP at 275 °C [34].…”
Section: Grain Size From 1 To 10 µMmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a high friction coefficient, poor resistance to abrasive wear, and a low hardness limit the possible areas of application of titanium alloys. Therefore, the proper use of these materials requires knowledge of their characteristics and properties [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%